Avaliação de danos genômicos em pacientes submetidos a hemodiálise, após suplementação vitamínica - Batista, Thatiane Lorena Miranda (2012)
Chronic renal failure (CRF) is increasingly common in the population and involves the irreversible loss of kidney function necessitating treatment of renal replacement therapy. The most common is hemodialysis that performs a bypass filtration, removing fluids and toxins from the blood of the patient. But this process does not physiological causes an increase in oxidative stress and complications such as diseases of morbidity and mortality among them the cardiovascular disease and cancer. For a reduction in the frequency of these diseases is achieved the use of vitamins is necessary because the nutritional status affects the development of these diseases. The aim of this study was to examine the genotoxicity and cytotoxicity in chronic renal patients using the micronucleus assay in lymphocytes and buccal mucosa cells after vitamin supplementation by folic acid and vitamins E, C and B12. There were 16 voluntary patients provided that each of the three samples for each test, a sample was received before supplementation and during the treatment, after one and two months of use of vitamins. In the assay of lymphocytes with blocking cytokinesis (CBMN) were analyzed nuclear buds, nucleoplasmic bridges and micronuclei in binucleated cells, and nuclear division index. Already in the cells of mucosa were binucleated cells, mononucleated and apoptosis, karyolysis, micronucleus and broken egg. The results show that the frequency of nuclear abnormalities was reduced with the use of vitamins in two trials, and in some assessments there were no statistical differences. In addition, were found gender differences in behavior of supplementation. This study provides evidence that vitamin use by patients with chronic renal failure was associated with reductions in nuclear changes evaluated, which may contribute to better quality of life for these patients.